PERANCANGAN DAN PEMBUATAN TEMPAT SAMPAH OTOMATIS BERBASIS SENSOR ULTRASONIK DI DLH KOTA YOGYAKARTA - Fatur Putra Ramadhan; Tri Novia Colling; Andung Jati Nugroho (KAMPUS AKADEMIK PUBLISING, 2026)
The amount of waste in urban areas, especially in Yogyakarta City, is growing, which shows the need for better and cleaner waste management. Traditional trash bins need people to touch them directly, which can make them less clean and uncomfortable to use. This study focuses on creating an automatic trash bin that opens and closes without touching, using an ultrasonic sensor. This system is being developed for the Yogyakarta City Environmental Agency (DLH). The system uses an ultrasonic sensor to sense when something is near, a microcontroller to control everything, and a servo motor to open and close the bin automatically. The research process includes reading previous studies, designing the system, building a prototype, and testing how well it works. The test results show that the system can accurately detect objects within a certain distance and operate the opening and closing function smoothly and quickly. Using this automatic trash bin can help make public spaces cleaner, more comfortable for users, and support the development of technology-based waste management solutions in Yogyakarta City.